CONTAMINATION LEVELS OF SELECTED ORGANOCHLORINE AND ORGANOPHOSPHOROUSPESTICIDES IN GHANAIAN FRUITS AND VEGETABLES - Bempah, Crentsil Kofi; Asomaning, Jacob Kofi; Ansong, Daniel Ayirebi; Asabere, Juliana Boateng and Stephen Boahen (Emirates Journal of Food and Agriculture, 2017)
A study was conducted to obtain systematic monitoring data on the contamination levels of selected organochlorine and organophosphorous pesticide residues in fruits and vegetables sold on Ghanaian markets. A total of 309 samples of fruits and vegetables were purchased from the main urban markets and supermarkets in Greater Accra through the months of July, 2009 to May, 2010. The analysis was carried out on GC-ECD employing multi residue analytical technique. The obtained results showed the predominance of methoxychlor in most of the analyzed samples. The detected concentrations of it in pineapple, lettuce, cabbage, cucumber and onion exceeded the European Commission Maximum Residue limits (EC MRLs), as did the concentrations of lindane in papaya, pineapple, cabbage and onion as well as dieldrin in papaya, banana, pineapple and cabbage. Residues of endrin in lettuce and carrot were higher than the EC MRL, as was chlorpyrifos in pineapple. Based on the observations made in these studies, it is proposed that more extensive investigations covering all foodstuffs in Ghana be carried out so as to generate data for policy making, development of consumer information laws and curtailment of the use of some of these pesticides.